PENGGUNAAN HISTORIOGRAFI TRADISIONAL JAWA UNTUK PENULISAN SEJARAH: Studi tentang Pengasingan Sunan Paku Buwana VI ke Ambon, 1830-1849 - Puguh, Dhanang Respati (Jurnal Sejarah Indonesia, 2024)
This article explains the use of Javanese traditional historiography proposed by Sartono Kartodirdjo. This article was prepared using the literature study method. The literature used is in the form of undergraduate theses, dissertations, and books prepared using and discussing Javanese traditional historiography. Overall, the chronicle about the exile of Sunan Paku Buwana VI in Ambon has a historical picture. The strength of this text as a historical source lies in its description of the mental turmoil and experiences of a king who was removed from his throne and had to live in exile. The existence of candra sengkala written following important events described in the chronicles further proves that these chronicles contain strong historical elements. In addition, as a historical source, the chronicle about Sunan Paku Buwana VI's exile contains important material not found in colonial archives.